Comparison of Terbuthylazine and Atrazine Preemergence in Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2020)
Terbuthylazine is an atrazine analog that is used in Europe as a replacement for atrazine. This study compares terbuthylazine with common herbicide tank mixes for weed control in this region. All herbicides controlled quinoa and crabgrass 95% or more, whereas Bicep II Magnum controlled kochia, Palmer amaranth, and Russian thistle the best late in the season. No herbicide visibly injured grain sorghum in this experiment. Grain yields increased 18 to 32 bu/a when herbicides were applied compared to the nontreated controls except with atrazine at 24 oz/a.
Keywords: triazine herbicides; residual control